A brief history of slavery - Black, Jeremy 1955- (Brief history of., 2011)
Slavery is as old as the world itself and expert and professor Jeremy Black will show that its history is one that is central to our understanding of the modern world. This essential guide is a new global history of slavery from ancient times to the present day, includes fascinating new insights and interpretations including the role of slavery within Islam, the complicity of some Africans in the transatlantic trade, and will raise key questions about the persistence of slavery today and what our governments are doing about it.--Publisher's description.